Trends and factors contributing to health facility delivery among adolescent women in Ethiopia: multivariate decomposition analysis - Asaye Alamneh Gebeyehu; Dejen Gedamu Damtie; Chalachew Yenew (BMC Women's Health, 2022)
Abstract Background Although an increase in health facility delivery in Ethiopia over time, adolescent women giving birth at health facilities is still low. Health facility delivery is crucial to improving the health of women and their newborns' health by providing safe delivery services. We aimed to examine the trend change and identify factors contributing to health facility delivery in Ethiopia. Methods We analyzed the data on adolescent women obtained from three Ethiopian Demographic and Health Surveys. A total of weighted samples were 575 in 2005, 492 in 2011, and 378 in 2016. Data management and further statistical analysis were done using STATA 14. Trends and multivariate decomposition analysis were used to examine the trends in health facility delivery over time and the factors contributing to the change in health facility delivery. Results This study showed that the prevalence of health facility delivery among adolescent women in Ethiopia increased significantly from 4.6% (95% CI 3.2–6.7) in 2005 to 38.7% (95% CI 33.9–43.7) in 2016. Decomposition analysis revealed that around 78.4% of the total change in health facility delivery over time was due to the changes in the composition of adolescent women and approximately 21.6% was due to the changes in their behavior. In this study, maternal age, place of residency, wealth index, maternal education, frequency of ANC visits, number of living children, and region were significant factors contributing to an increase in health facility delivery over the study periods. Conclusion The prevalence of health facility delivery for adolescent women in Ethiopia has increased significantly over time. Approximately 78.4% increase in health facility delivery was due to adolescent women’s compositional changes. Public health interventions targeting rural residents and uneducated women would help to increase the prevalence of health facility delivery.